The Analysis of Live-Attenuated Piscirickettsia Salmonis Vaccine Reveals the Short-Term Upregulation of Innate and Adaptive Immune Genes in Atlantic Salmon (Salmo Salar): An in Situ Open-Sea Cages Study - Sandino-Garcia, A; Imarai-Bahamonde, C; Acuna-Castillo, C; Vargas-Valenzuela, D; Vallejos-Vidal, E (Multidisciplinary Digital Publishing Institute (MDPI), 2021)
Piscirickettsia salmonis, the etiological agent of the Salmon Rickettsial Septicemia (SRS), is one the most serious health problems for the Chilean salmon industry. Typical antimicrobial strategies used against P. salmonis include antibiotics and vaccines, but these applications have largely failed. A few years ago, the first attenuated-live vaccine against SRS (ALPHA JECT LiVac® SRS vaccine) was released to the market. However, there is no data about the agents involved in the activation of the immune response induced under field conditions. Therefore, in this study we evaluated the expression profile of a set of gene markers related to innate and adaptive immunity in the context of a cellular response in Atlantic salmon (Salmo salar) reared under productive farm conditions and immunized with a live-attenuated vaccine against P. salmonis. We analyzed the expression at zero, 5-, 15-and 45-days post-vaccination (dpv). Our results reveal that the administration of the attenuated live SRS LiVac vaccine induces a short-term upregulation of the cellular-mediated immune response at 5 dpv modulated by the upregulation of ifnα, ifnγ, and the cd4 and cd8α T cell surface markers. In addition, we also registered the upregulation of il-10 and tgfβ. Altogether, the results suggest that a balanced activation of the immune response took place only at early times post-vaccination (5 dpv). The scope of this short-term upregulation of the cellular-mediated immune response against a natural outbreak in fish subjected to productive farm conditions deserves further research. © 2021 by the authors. Licensee MDPI, Basel, Switzerland.